Fator estocástico de desconto: as cotas de variância, métricas de distância e suas extensões - Araújo, João Bretas de (2010)
The concept of stochastic discount factor pervades the Modern Theory of Asset Pricing. Initially, such object allows unattached pricing models to be discussed under the same terms. However, Hansen and Jagannathan have shown there is worthy information to be brought forth from such powerful concept which undelies asset pricing models. From security market data sets, one is able to explore the behavior of such random variable, determining a useful variance bound. Furthermore, through that instrument, they explore one pitfall on modern asset pricing: model misspecification. Those major contributions, alongside with some of its extensions, are thoroughly investigated in this exposition.